ESTIMATION OF BALLISTIC PARAMETERS OF GUN PROPELLANTS THROUGH CLOSED VESSEL EXPERIMENT MODELING - de Oliveira, J. L. S. P.; Filho, A. A. M. F.; Platt, G. M.; Peixoto, F. C. (Revista de Engenharia Térmica, 2005)
Closed vessels have being used for the regression of lumped ballistic parameters for decades. However, if material and energy balances are coupled with burning rate empirical correlations, several uncorrelated parameters can be estimated, which describe more accurately the thermochemical behavior of the gases generated, even if the chemical composition of the propellant is unknown (as when the propellant is aged, for instance). This research presents such approach leading to a system of differential equations which are integrated to produce a theoretical pressure profile in the vessel, highly dependent on the choice of empirical parameters. Such parameters are manipulated according to the Maximum Likelihood statistical procedure, which leads to the best set of parameters to describe the propellant.